Analisis ekowisata garam di Kabupaten Sumenep: pendekatan Triple Helix - Triana Setiyarini; Yustina Chrismardani (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2022)
One of the solutions offered to overcome the economic problems faced by salt farmers in Sumenep Madura is salt ecotourism. The research objective was to find out the right strategy formulation in exploring the potential of salt ecotourism in Sumenep Regency through a SWOT analysis (analysis of strengths and weaknesses as well as opportunities and challenges that will be faced). The primary data is taken from interviews and questionnaires involving the role of academia, business and government which is known as the triple helix. The results of the study show that Kertasada Village has strong internal resources and has opportunities from strong external factors to realize salt ecotourism.